Pendampingan Perancangan Gudang Material dan Cutting pada Perusahaan Tas TIJ - Emelia Sari; Didien Suhardini; Tiena Gustina Amran; Iveline Anne Marie; Annisa Dewi Akbari; Isnaeni Nabilah; Andi Arni Soraya; Nur Azizah Putri Utami (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Top Intera Jaya (TIJ) is a company that focuses on designing and producing high-quality leather bags, wallets, and accessories. TIJ has a monthly production capacity of 50,000 pcs and plans to increase it to 100,000. The company needs better storage capacity and production floor to support this increase. This Community Service Program (CSP) aims to assist TIJ in redesigning the production floor into a raw material and cutting storage warehouse using the shared storage method. The shared storage method organizes warehouse space using the FIFO (First In First Out) principle, where the fastest delivered items are placed in the storage area closest to the exit. This CSP began by conducting interviews with resource persons, namely warehouse staff, to understand the needs of TIJ. After getting an initial overview, the team designed the training materials that TIJ needed. CSP was conducted on February 2, 2024, with the pre-test and post-test results showing an increase in participants' understanding of warehouse design from 33% to 67% and from the results of the training and mentoring, the team and management of TIJ agreed that the shared storage method with the FIFO principle is the best solution that will be implemented for warehouse layout efficiency at TIJ.